Sex differences in prevalence and determinants of hypertension among adults: a cross-sectional survey of one rural village in Bangladesh - Jessica Yasmine Islam; M Mostafa Zaman; Jasim Uddin Ahmed; Sohel Reza Choudhury; Hasanuzzaman Khan; Tashfin Zissan (BMJ Open)
Objective Prevention of mortality due to cardiovascular disease (CVD) through control of hypertension is a public health priority in Bangladesh. Our objective was to assess sex differences in prevalence and determinants of hypertension among adults in one rural area of Bangladesh.Study design Cross-sectional.Setting and participants From January 2014 to December 2015, we conducted a cross-sectional study of 2600 men and women aged ≥18 years located in one rural district of Bangladesh. We collected data on demographics, behavioural factors, physical measurements and health history.Primary outcome measures Our primary outcome was hypertension (systolic blood pressure ≥140 or diastolic blood pressure ≥90 mm Hg).Results The average age of participants was 41.6 years and 53.7% were women. Hypertension prevalence was 6.9% (95% CI 5.9 to 7.9), and was significantly higher among women (8.9%) than men (4.5%). The highest prevalence of hypertension was observed among women aged ≥60 years at 21.3% (95% CI 16.6 to 26.7). A higher proportion of men with hypertension were aware of their condition (72.2%) compared with women (52.4%). Determinants of hypertension included older age, higher education, current tobacco use, increasing body mass index, and hyperglycaemia.Conclusion Our research suggests that hypertension prevalence is higher among women than men in rural Bangladesh. Sex-specific interventions should be developed to inform adults of the necessary lifestyle changes that may reduce the risk of hypertension and subsequent CVDs.